PEDAGOGY IN MEDICAL RESIDENCY TRAINING OF PEDIATRICIANS - Elena N. Grinko (Вопросы современной педиатрии)
The training program for a modern pediatrician involves the study of Pedagogy in medical residency in specialty 31.08.19 Pediatrics. The urgency of such training for the future doctor is uncontroversial today. Currently the experience of studying this discipline has been gained in Russian medical universities. At the same time this work requires further improvement and exchange of experience with colleagues.